MBORAYU, o espírito que nos une: um conceito da espiritualidade guarani - Pereira, João José de Félix (2010)
In this text, I deal with a concept of the spirituality of the Guarani people, which is the "Mborayu", the spirit-force: that integrates and disintegrates the elements that make up the Ñande Reko (the Guarani way of being); that agglutinates or disperses the elements and bodies (rete kwere) that make up the individual; which catalyzes or dilutes Ñamandu (the nature of all worlds). The "Mborayu" also encompasses the Aywu (the word) that names and organizes an understanding of the Ñeem (term-idea), of the spirit of things, which is not reality (ete), because the ultimate reality (opa'wa'erã ) belongs to Ñemi'Guaxu (the great mystery). In this tone, I go through in this study, a whole universe of mythical and Guarani spirituality, because the "Mborayu" brings together all the elements that make up Ñamandu, in an unfinished totality and, by its force of attraction, life (ikowe) is generated, finding , however, its last expression, in death (bro), in disintegration, its ultimate meaning.(AU)